PENINGKATAN PERTUMBUHAN TANAMAN JAGUNG ( Zea mays L.) MENGGUNAKAN JAMUR MIKORIZA ARBUSKULAR DARI JENIS YANG BERBEDA PADA KONDISI CEKAMAN AIR - isna isna; Wahyu Harso; Yusran Yusran (Biology Department, Mathematics and natural science, Tadulako University, 2020)
Arbsucular mycorrhizal fungi promote plant growth by enhancing mineral uptake. Contribution degree of arbuscular mycorrhizal fungi to promote plant growth depend on species of plant-fungus association. The aim of this study was to compare the ability of three species of Glomus to promote maize plant growth. Maize plants were inoculated with 20 g inoculum of either Glomus deserticola, Glomus etunicatum, or Glomus clorum. Inoculum was soil containing spore, hyphae and infected root. Maize plants without addition inoculum were also used as a control. Water availability in the soil as growing medium was maintained on 40% field capacity. The results showed that addition of inoculum from three species of Glomus increased average of maize plant shoot dry weight although there was no statisticaly significant differences. Maize plant inoculated with G. clorum had higher shoot dry weight than maize plant inoculated either with G. etunicatum or G. deserticola while root colonization by G. clorum was lowest.